Simulações do tratamento antirretroviral em populações com estrutura de idades - Ferreira, Douglas Santos Rodrigues (2010)
In this work, we try to model the dissemination process of the Human Immunodeficiency Virus, HIV, in age-structured populations, by using population dynamics tools. Firstly, we present a historical and biological review of the biology of the viruses responsible for Human Immunodeficiency Syndrome, AIDS, and their implications in the human body and their transmission to other individuals. In addition, we also present some basic concepts relevant to the study of networks. Secondly, we propose a computer model for reproducing the epidemiological effects in environments with and without treatments to combat the virus. To develop the model we use both the Penna model for biological aging and the theory of networks for the set of sexual relationships.. The distribution of connections, symbolizing the sexual contacts, is made through the random networks, and performing measurements of some quantities characteristics of networks, such as distributions of groups and the connectivity of individuals. Some preliminary results for complex networks are also presented.